Evaluación del grado de Bienestar Animal a causa de la Covid 19 en perros domésticos (Canis lupus familiaris) en la Parroquia la Asunción Provincia Bolívar. - Becerra Segura, Cristian Marcelo (2022)
The present investigation is carried out in the parish of La Asunción and was born under the objective of evaluating the degree of Animal Welfare based on compliance with the five freedoms before and after the pandemic in domestic dogs (Canis lupus familiaris) in the Parish, due to Because the habits of owners and their pets have drastically changed, in this sense, for this purpose, a qualitative and quantitative approach methodology has been developed with the use of an assessment sheet with polytomous and dichotomous questions in order to characterize the parish pets and determine the physical and psychological state based on the analysis of the five freedoms, as well as identify the most important indicators that predict animal welfare, the type of study is non-experimental, its purpose is exploratory and descriptive , to determine the number of users to survey, the formula for finite populations was applied, resulting in 175 users who they have pets. The results denote a deterioration of animal welfare and the physical and psychological state of the pets, going from 83% to 65% in good condition, under the analysis of Chi square and Pearson's test to measure correlation and association of variables, the indicators of higher incidence are: the character of tranquility shown with an association value of 0.963, quality of food with 0.879, quantity of food with 0.589, quality and access to water with 0.818, way of caring for the pet when diseases appear with 0.843 and diseases in pets with 0.583. These data allowed a causality model to be carried out under the statistical test of multiple linear regression that explains which indicators affect animal welfare by 0.854, considered very high.